Fucosylated chondroitin sulphate from sea cucumber inhibits high-fat-sucrose diet-induced apoptosis in mouse pancreatic islets via down-regulating mitochondrial signaling pathway - Shiwei Hu; Jingfeng Wang; Hui Xu; Yuming Wang; Zhojie Li; Changhu Xue (Journal of Functional Foods, 2014)
Hyperglycaemia can induce pancreatic islets apoptosis. We previously found that fucosylated chondroitin sulphate from Cucumaria frondosa (Cf-CHS) exhibited anti-hyperglycaemic effects; however, its effects on pancreatic islets are lacking. This study investigated the effects of Cf-CHS on inhibition pancreatic islets apoptosis in high-fat high-sucrose diet (HFSD)-induced insulin resistant mice for 19 weeks. Results showed that Cf-CHS significantly repaired HFSD-injured pancreatic islets, decreased blood glucose, insulin, TNF-α levels, and increased adiponectin level. Cf-CHS significantly reduced Bid, Bax, cytochrome c, caspase 9, and caspase 3 mRNA expressions, and increased Bcl-2 and Bcl-xL mRNA expressions. Cf-CHS also caused significant down-regulation of t-Bid, Bax, cytochrome c in cytoplasm, caspase 9, and cleaved-caspase 3 proteins, and up-regulation of Bcl-2 and Bcl-xL proteins. Furthermore, Cf-CHS enhanced the effects of rosiglitazone (RSG). These indicate that Cf-CHS inhibits pancreatic islets apoptosis via inhibition mitochondrial pathway. These findings may provide a dietary intervention hyperglycaemia-induced pancreatic islets apoptosis.